STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH (Studi kasus U.D Tarsius Kelurahan Kinali Kecamatan Kawangkoan) - Ribka S. Laloan; Caroline D.B Pakasi; Olfie L.S Benu (COCOS, 2016)
ABSTRACTThe role of small businesses become part foremost in any planning for local development. However, the development effort that has been carried out is still not satisfactory result, because in reality the progress of UKM are seen in comparison with the progress already achieved a great effort. The purpose of this study was identifying the strengths, weaknesses, opportunities and threats U.D Tarsius in business development and to define strategies for UKM development U.D Tarsius.Peanut roaster UD Tarsius Kawangkoan established since 2002, and the condition of UKM them selves do not seem to change significantly from year to year or can be said is still undeveloped, seen the production process, the management comes to marketing that still use traditional materials, see the situation are there then be interesting to be investigated how this business development strategy.The data collection was conducted over three months from November to January 2016 data taken is the primary and secondary data, primary data obtained through interviews to the owner U.D Tarsius and secondary data based on the data that already exists in U.D Tarsius.Research shows that small and medium enterprise development strategy U.D tarsier is the agrisif strategy is to maintain the strength to overcome the weaknesses in it and also have the opportunity and the power to be developed.Keywords : MinahasaABSTRAK